13-4b+6b-5=

Simple and best practice solution for 13-4b+6b-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-4b+6b-5= equation:


Simplifying
13 + -4b + 6b + -5 = 0

Reorder the terms:
13 + -5 + -4b + 6b = 0

Combine like terms: 13 + -5 = 8
8 + -4b + 6b = 0

Combine like terms: -4b + 6b = 2b
8 + 2b = 0

Solving
8 + 2b = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 2b = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 2b = 0 + -8
2b = 0 + -8

Combine like terms: 0 + -8 = -8
2b = -8

Divide each side by '2'.
b = -4

Simplifying
b = -4

See similar equations:

| 2.8+4.7x=-35.74 | | Y-8.7=2.3 | | (4x-7)=18 | | 0=81-x^2 | | 332/64=m | | 3.7b-0.92=-37.92 | | 39-y=223 | | 47+2x+3=90 | | -50+3k=-11 | | 3(-5)+2= | | (2x+7)=18 | | 3(x-2)=6(x-1)-3x | | 10r^2=400 | | F(x)=130x-.02x^2 | | -2.6x+1.1=14.1 | | 2d+10=2(d-8) | | 48+5x-3=90 | | -5x+10y+5x-10y=36 | | (b+3)3=(b-3)4 | | (2x+7)+(4x-7)=180 | | 5y-9=9y+10-4y | | 2n-20=66 | | 3.1x+5.2=9.9Q | | -2y+13x=10 | | 4x-12+2x=24 | | y=3y-13 | | 8+10x^2=-22 | | 2x^2-12x+16=30 | | 4x+2y+3x-2y=25 | | 5A+8b=15820 | | 5-4n=33 | | 7(w-1)-9=-5(-6w+2)-9w |

Equations solver categories